J-Potential in Classical Thermodynamics and Its Application to a Critical Vapor Bubble in a Metastable Liquid - Rusanov, Anatoly I.; Shchekin, Alexander K.; Tatyanenko, Dmitry V. (Fine Chemical Engineering, 2025)
The article introduces the reader to the thermodynamic potential of classical thermodynamics, called the J-potential. It can be generally defined as the grand thermodynamic potential plus the volume of the system multiplied by some pressure (which may be the external pressure, the pressure in one of the phases in a multiphase system). Variants of the J-potential are considered. It is shown that the J-potential is perfectly suited for multiphase (heterogeneous) systems. In this work, it is applied to study the dependence of the chemical potential of a substance in a small vapor bubble, formed in the bulk liquid, on the bubble size.